2021
DOI: 10.1039/d1dt01634b
|View full text |Cite
|
Sign up to set email alerts
|

A study on the influence of ligand variation on formamidinate complexes of yttrium: new precursors for atomic layer deposition of yttrium oxide

Abstract: The synthesis and characterization of a series of closely related Y(III) compounds comprising the formamidinate ligands (RNCHNR) (R = alkyl) is reported, with the scope of using them as prospective...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…The considerably lower onset temperature of evaporation and melting point for [Ir(COD)(DPfAMD)] might be explained by a lower degree of intermolecular van-der-Waals interactions due to the smaller endocyclic (-H) substituent and is moreover in line with our previous studies on yttrium formamidinate complexes. [37,38] The onset temperature of decomposition derived by DSC from our TG measurements is the lowest (176 °C) for [Ir(COD)(DPfAMD)], followed by [Ir(COD)(DPDMG)] (198 °C) and [Ir(COD)(DPAMD)] (211 °C). The differences seen in the decomposition points of the complexes is further supported by the high residual weights seen for all the complexes, while [Ir(COD)(DPfAMD)] features the highest residual weight of 58.0 % after subsequent heating to 550 °C.…”
Section: Thermal Evaluationmentioning
confidence: 91%
See 1 more Smart Citation
“…The considerably lower onset temperature of evaporation and melting point for [Ir(COD)(DPfAMD)] might be explained by a lower degree of intermolecular van-der-Waals interactions due to the smaller endocyclic (-H) substituent and is moreover in line with our previous studies on yttrium formamidinate complexes. [37,38] The onset temperature of decomposition derived by DSC from our TG measurements is the lowest (176 °C) for [Ir(COD)(DPfAMD)], followed by [Ir(COD)(DPDMG)] (198 °C) and [Ir(COD)(DPAMD)] (211 °C). The differences seen in the decomposition points of the complexes is further supported by the high residual weights seen for all the complexes, while [Ir(COD)(DPfAMD)] features the highest residual weight of 58.0 % after subsequent heating to 550 °C.…”
Section: Thermal Evaluationmentioning
confidence: 91%
“…The starting material N,N'-Diisopropylformamidine was synthesized according to literature-known procedures. [37] NMR measurements were performed on a Bruker Avance III 300 and DPX-200 spectrometers in capped NMR tubes with degassed and dried deuterated solvents. EA measurements (CHN) were performed on a Vario Micro Cube from Elementar Analysensysteme GmbH, while the sample preparation was conducted inside the glovebox to minimize the exposure to the ambient.…”
Section: Methodsmentioning
confidence: 99%
“…Commercially available reagents were used without further purification. The starting material N,N ′-diisopropylformamidine was synthesized according to literature-known procedures . NMR measurements were performed on a Bruker Avance III 300 and DPX-200 spectrometers in capped NMR tubes with degassed and dried deuterated solvents.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 summarizes the theoretical-study-only ALD articles found in the Web of Science and covered in this review. It is worth mentioning that this review mostly focuses on the theoretical-study-only ALD articles and does not cover the combined experimental and theoretical ones, which are cited here [ 75 , 76 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ]. Figure 5 displays the publications, summarized in Table 2 , that are covered in this study.…”
Section: Theoretical Studies On Aldmentioning
confidence: 99%